Improving Mental Health and End-of-Life Care in Residents of Nursing Homes: A Cluster Randomized Clinical Trial of Efficacy (COSMOS), 2015 - Husebø, Bettina S. (NSD – Norwegian Centre for Research Data, 2018)
Nursing home (NH) patients have complex mental health problems, disabilities and social needs, compounded by widespread prescription of psychotropic drugs. To preserve their dignity and quality of life (QoL) is an important goal. This can only be achieved within NHs that offer high competent conditions of treatment and care. COSMOS is a practical intervention aimed to improve clinical and psychiatric challenges in NH patients. The COSMOS intervention combined most effective research results to improve staff competence, and patients' mental health, safety, QoL, and to reduce medication use and costs. The efficacy testing of COSMOS included systematic literature review, a 3 months pilot study, 9-month cluster randomized clinical trial (RCT), and the development of manuals and education of trained NH therapists. Quantitative measures were collected at baseline, month 4, and 9. Four Ph.D students and a postdoctoral candidate were educated as data collectors. 380 patients, =65 years, were recruited from 40 NHs in Bergen, Stavanger, Bærum, Sarpsborg, Fredrikstad and Tromsø. NHs were randomized to either COSMOS or current best practice. Primary and secondary outcome measures CMAI, QUALID, QoL-AD, EQ-5D and cost-utility analysis (RUD-FOCA); NPI-NH; ADL; Cornell; MOBID-2; psychotropic drug use; drug-related problems; pain and symptom management; hospital admission, and mortality. To investigate sleep problems and circadian misalignment Actigraph assessments will be used and fastened around the participants' non-dominant arm. The data includes data collected at baseline, month 4 and month 9. MOBID2 mapping scheme was used for mapping pain at the different measurement times. Questionnaires were sent out to relatives at baseline and month 4.